2022
DOI: 10.1007/s43630-021-00163-2
|View full text |Cite
|
Sign up to set email alerts
|

Proton-controlled Action of an Imidazole as Electron Relay in a Photoredox Triad

Abstract: Electron relays play a crucial role for efficient light-induced activation by a photo-redox moiety of catalysts for multi-electronic transformations. Their insertion between the two units reduces detrimental energy transfer quenching while establishing at the same time unidirectional electron flow. This rectifying function allows charge accumulation necessary for catalysis. Mapping these events in photophysical studies is an important step towards the development of efficient molecular photocatalysts. Three mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…We are happy to announce that today, this virtual volume unites 18 contributions by scientists from 17 countries (Canada, Czech republic, Finland, France, Germany, Hungary, India, Italy, Japan, Lebanon, Poland, Russia, Spain, Switzerland, Taiwan, UK, US) touching upon the wide variety of the subjects dealt with by Klaus at various times [25,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143].…”
Section: Legacy Tribute Continuation…mentioning
confidence: 99%
See 1 more Smart Citation
“…We are happy to announce that today, this virtual volume unites 18 contributions by scientists from 17 countries (Canada, Czech republic, Finland, France, Germany, Hungary, India, Italy, Japan, Lebanon, Poland, Russia, Spain, Switzerland, Taiwan, UK, US) touching upon the wide variety of the subjects dealt with by Klaus at various times [25,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143].…”
Section: Legacy Tribute Continuation…mentioning
confidence: 99%
“…Three more papers deal with chemical model systems for light-induced electron transfer [138][139][140]. Gotico [139].…”
Section: Legacy Tribute Continuation…mentioning
confidence: 99%
“…However, the spectra for all Ru-Im-xMe-PhOH complexes are clearly distinct from the spectra induced under the same conditions in the reference compound Ru-Im-Ph, where no fast phase is observed (Figure 4C, S7) and where ligand oxidation leads to formation of an imidazolyl radical with spectral features very similar to those observed in a Ru-Imi-terpyridine complex. [21] These observations are taken as evidence for the involvement of the phenol group in all Ru-Im-xMe-PhOH compounds. It can thus be concluded that in the Ru-Im-xMe-PhOH compounds a radical is formed, characterized by relatively strong absorption around 850 nm and in the 350-550 nm region, and which involves both the phenol and the imidazole groups.…”
Section: Transient Absorption Propertiesmentioning
confidence: 97%
“…[20] The differences in lifetime and emission yield between the three complexes is tentatively explained by a weak, substitutiondependent photoacid behavior of the phenanthroline-imidazole ligand attributed to electrostatic interaction between the positive charge on the Ru ion and the imidazole group. [21]…”
Section: Absorption and Emission Propertiesmentioning
confidence: 99%
“…Reduced 10 then diffuses to the catalyst and transfers one electron, thus leading to unidirectional electron flow. It has been shown previously that electron relays can facilitate both charge separation and efficient electron transfer between PS and catalyst. , A TOF = 23 h –1 and TON = 58 after 200 min of irradiation is obtained, which is significantly higher than the reference system (complex without cage; TOF = 1 h –1 and TON = 6).…”
Section: Coordination Cages For Artificial Photosynthesismentioning
confidence: 99%